Does government ideology affect personal happiness?: a test - Dreher, Axel; Öhler, Hannes (Economics letters, 2011)
We investigate the impact of government ideology on left-wing as compared to conservative individuals. We find that conservative people are happier, on average. In a sample excluding the richest countries left-wing people are happier under the tenure of left-wing governments.